2018
DOI: 10.15298/invertzool.15.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in pre-feeding larvae of sea urchins, Mesocentrotus nudus and Strongylocentrotus intermedius

Abstract: Experimental studies showed that in echinoids egg size of a species affects magnitude of phenotypic plasticity in larvae of the species. Here we tested whether any difference in magnitude of plasticity exists in pre-feeding larvae of two sea urchins, Mesocentrotus nudus (A. Agassiz, 1864) and Strongylocentrotus intermedius (A. Agassiz, 1864). These species are closely related by their phylogenetic position, have overlapping ranges, and differ by size of their eggs. Our results indicate that by the end of pre-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(43 reference statements)
4
6
0
Order By: Relevance
“…Many studies of phenotypic plasticity in echinoid larvae assumed that when developing in food-limited environment the larvae invest Earlier we found that larvae of these sea urchins differed from one another in the magnitude of post-oral arm growth depending on concentration of microalgae in the water. Our results (Kalachev et al, 2018) indicate that M. nudus larvae grown under low-and high-algae conditions had shorter post-oral arms by 5% and 9%, respectively, as compared with their siblings from the no-algae group. On the contrary, S. intermedius larvae grown under low-and high-algae condition had their post-oral arms by 2% and 13% shorter, respectively, than those in the larvae from the no-algae group (Kalachev et al, 2018).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Many studies of phenotypic plasticity in echinoid larvae assumed that when developing in food-limited environment the larvae invest Earlier we found that larvae of these sea urchins differed from one another in the magnitude of post-oral arm growth depending on concentration of microalgae in the water. Our results (Kalachev et al, 2018) indicate that M. nudus larvae grown under low-and high-algae conditions had shorter post-oral arms by 5% and 9%, respectively, as compared with their siblings from the no-algae group. On the contrary, S. intermedius larvae grown under low-and high-algae condition had their post-oral arms by 2% and 13% shorter, respectively, than those in the larvae from the no-algae group (Kalachev et al, 2018).…”
Section: Discussionsupporting
confidence: 46%
“…Our results (Kalachev et al, 2018) indicate that M. nudus larvae grown under low-and high-algae conditions had shorter post-oral arms by 5% and 9%, respectively, as compared with their siblings from the no-algae group. On the contrary, S. intermedius larvae grown under low-and high-algae condition had their post-oral arms by 2% and 13% shorter, respectively, than those in the larvae from the no-algae group (Kalachev et al, 2018).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Morphological plasticity is well-described in echinoderm larvae (36,37,39) [Reviewed in (34,35)]. In this study, we found that the sizes of multiple larval structures were associated with differences in bacterial exposure during development.…”
Section: Bacterial Exposure-associated Morphological Plasticitysupporting
confidence: 52%
“…Planktotrophic larvae tend to undergo a plastic response to fluctuating food availability. Specifically, under low-food conditions, the lengths of the larval arms, used for feeding, are increased relative to larval body length, while overall gut volume is reduced (35)(36)(37)(38)(39). Recently, Carrier and Reitzel (28) correlated feeding-induced plasticity with structural changes in the associated bacterial microbiota of three confamilial sea urchins (S. purpuratus, S. droebachiensis, and Mesocentrotus franciscanus), underscoring a role for microbes in larval development (19,31).…”
Section: Introductionmentioning
confidence: 99%